Epstein-Barr Virus Reactivation after Infliximab in Rheumatoid Arthritis: A Case Report - Michele Colaci; Marco Sebastiani; Gilda Sandri; Marisa Meacci; Clodoveo Ferri (Case Reports in Infectious Diseases)
TNF-alpha blockers represent one of the most important therapeutic strategies for rheumatoid arthritis, but their use has raised the question about their safety profile, particularly in respect to viral infections/reactivations. We describe the case of a patient who developed a symptomatic EBV reactivation 11 days after the first infusion of infliximab.